The design basis for the integrated and continuous biomanufacturing framework. Issue 9 (11th May 2021) - Coffman, Jon; Bibbo, Kenneth; Brower, Mark; Forbes, Robert; Guros, Nicholas; Horowski, Brian; Lu, Rick; Mahajan, Rajiv; Patil, Ujwal; Rose, Steven; Shultz, Joseph
Abstract: An 8 ton per year manufacturing facility is described based on the framework for integrated and continuous bioprocessing (ICB) common to all known biopharmaceutical implementations. While the output of this plant rivals some of the largest fed‐batch plants in the world, the equipment inside the plant is relatively small: the plant consists of four 2000 L single‐use bioreactors and has a maximum flow rate of 13 L/min. The equipment and facility for the ICB framework is described in sufficient detail to allow biopharmaceutical companies, vendors, contract manufacturers to build or buy their own systems. The design will allow the creation of a global ICB ecosystem that will transform biopharmaceutical manufacturing. The design is fully backward compatible with legacy fed‐batch processes. A clinical production scale is described that can produce smaller batch sizes with the same equipment as that used at the commercial scale. The design described allows the production of as little as 10 g to nearly 35 kg of drug substance per day. Abstract : An 8 ton per year manufacturing facility is described based on the framework for integrated and continuous bioprocessing (ICB) common to all known biopharmaceutical implementations. The equipment and facility for the ICB framework is described in sufficient detail to allow biopharmaceutical companies, vendors, contract manufacturers to build or buy their own systems. The design will allow the creation of a global ICB ecosystem that will transform biopharmaceutical manufacturing.